1991
DOI: 10.1073/pnas.88.9.3579
|View full text |Cite
|
Sign up to set email alerts
|

A site-specific deletion in mitochondrial DNA of Podospora is under the control of nuclear genes.

Abstract: In the filamentous fungus Podospora anserina, the association of two nuclear genes inevitably leads to a "premature death" phenotype consisting of an early end of vegetative growth a few days after ascospore germination. Mycelia showing this phenotype contain a mitochondrial chromosome that always bears the same deletion. One of the break points is exactly at the 5' splice site of a particular mitochondrial intron, suggesting that the deletion event could result from molecular mechanisms also involved in intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
5

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 44 publications
2
50
0
5
Order By: Relevance
“…Electron microscopy indicates no structural mitochondrial anomalies, and all mitochondria show a cytochrome oxidase activity for any type of tissue (15). This mutant thus survives substantial alterations to most of its mitochondrial genomes, a phenomenon that gives rise to severe pathological consequences in man or has been correlated with premature death in Podospora anserina (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Electron microscopy indicates no structural mitochondrial anomalies, and all mitochondria show a cytochrome oxidase activity for any type of tissue (15). This mutant thus survives substantial alterations to most of its mitochondrial genomes, a phenomenon that gives rise to severe pathological consequences in man or has been correlated with premature death in Podospora anserina (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear mutations that promote elevated rates of plastid mutations have been reported in petunia (Potrykus, 1970), Oenothera (Epp, 1973;Chiu et al, 1990), and maize (Thompson et al, 1983). Nuclear genes that control mitochondrial rearrangements are known in humans (Zeviani et al, 1989) and fungi (SeideCRogol et al, 1989;Belcour et al, 1991). In plants, there is evidence that the nuclear genetic background affects the frequency of mitochondrial genome rearrangements (Laughnan and GabayLaughnan, 1983;Newton and Coe, 1986), and at least one nuclear gene has been identified that is responsible for the loss of specific DNA sequences from the mitochondrial genome (Mackenzie and Bassett, 1987;Mackenzie and Chase, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…It is known from previous studies that phenotypic differences exist between the S mat+ and S mat2 mycelia of P. anserina S strain. For example, S mat+ and S mat2 grow at the same rate as S mat+/mat2, yet the S mat2 strain presents a shorter life span than the S mat+ strain (Marcou 1961), a differential suppression of the su8-1 suppressor tRNA (Silar et al 2000), triggers the "premature death" syndrome more frequently (Belcour et al 1991) and is slightly more thermoresistant (Contamine et al 2004). More recently, genome-wide microarray analysis revealed that many genes are differentially transcribed in S mat+ and S mat2 strains (Bidard et al 2011).…”
mentioning
confidence: 99%